Spontaneous Housing In Sana’a, Yemen – Case Studies - Abdoulkarim Al-Ansi, Nashwan; Wan Badaruzzaman, Wan Hamidon; Wahid, Julaihi; Md. Darus, Zuhairuse (2008)
The influx of rural population after the Yemen’s revolution in the early sixties, the union between North and South Yemen in the early nineties, and the returning of the war veterans after the second Gulf war in 1991 have contributed to many spontaneous and unorganized housing settlement areas that are not equipped with basic necessities.